Kajian Kelelahan pada Pengemudi Tank Menggunakan Pittsburgh Sleep Quality Index (Studi Kasus di Pusat Pendidikan Kavaleri) - Feriaty, Syarah Rizkia; Iridiastadi, Hardianto; Permana, Sigit; Sukmada, Uman (DPPM UNIVERSITAS PELITA BANGSA, 2023)
Fatigue is an important factor that contributes to the decline in someone's performance. This study aims to identify how much influence the duration of driving a combat vehicle has on the decline in cognitive function. A total of 8 TNI-AD soldiers were asked to drive a combat vehicle within 2 hours, and tested by subjective measurements using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. In this research, concluded that driving a combat vehicle within 2 hours resulted in a decrease in cognitive function. Then, it can also be concluded that most of the soldiers had good sleep quality after being measured through the PSQI questionnaire. The experimental results show that the number of respondents who have good sleep quality is 75%.